Curie-point depths, geothermal gradients and sub-surface heat flow estimation from spectral analysis of high-resolution aeromagnetic data over Gongola Basin and its environs, Northeastern Nigeria - Abubakar Yusuf; Lim, Hwee San; Ismail Ahmad Abir (Penerbit Universiti Kebangsaan Malaysia, 2022)
Geothermal energy resources have been established globally to be among the sustainable and environmentally harmless means of energy generation. Curie-point depths (CPD), temperature gradients, and heat flow data over the study area were computed using a spectral analysis method in order to have a preliminary view of the geothermal implications (prospect) of the current area. Aeromagnetic data acquired by the Nigerian Geological Survey Agency (NGSA) in the year 2009 was used for the research. The results showed the minimum, maximum, and the average CPD values as 8.18 km, 31.48 km, and 13.0 km, respectively. The minimum, maximum and average thermal gradients obtained were 18.42 °C/km, 70.91 °C/km, and 50.2 °C/km, respectively. The heat flow data obtained ranged from 33.15 mW/m2 to 177.28 mW/m2, with an average value of 110.65 mW/m2. Locations depicting shallow CPDs anomalies (Alkaleri, Darazo, Dukku, Misau, Wuyo, Deba, and Tula), also showed conformity with high heat flow areas. As such, they are regarded as areas of promising geothermal prospects and are recommended for further detailed investigation. Locations depicting a high magnetic susceptibility contrast from a generated analytic signal map, as well as high temperature gradients, high heat flow, and shallow CPDs are attributed to crustal thinning along the sedimentary basin and magmatic intrusions along basement areas, respectively. The magnetic depth to the basement calculated for the study area using the source parameter imaging (SPI) method ranges from 0.610 km to 3.055 km. The present study has provided an insight on preliminary information, regarding new areas of possible geothermal prospects for further detailed investigation.